Primary Umbilical Endometriosis A Case Report - Shrestha, Nira Singh; Pande, Shashi; Joshi, Mukunda; Padhye, SM (Nepal Journal of Obstetrics and Gynaecology, 2011)
A 32 year old, Para 2 with normal vaginal delivery presented with cyclical bleeding from a dark brown painful umbilical nodule for 6 months. The ultra sonogram showed a subcutaneous nodule at the umbilicus without any other abnormality. FNAC of the nodule diagnosed it as a case of umbilical endometriosis. A diagnostic laparosopy ruled out any associated pelvic endometriosis. Umbilectomy was done for the treatment of the condition. Keywords: Endometriosis, Umbilicus, Umbilectomy DOI: http://dx.doi.org/10.3126/njog.v6i1.5253 NJOG 2011; 6(1): 51-52